Electrochemical syntheses of nanomaterials and small molecules for electrolytic hydrogen production - Wei, Jiaqi (2023)
Hydrogen is a clean, efficient, renewable energy resource and the most promising alternative to fossil fuels for future carbon-neutral energy supply. Therefore, sustainable hydrogen production is highly attractive and urgently demanded, especially via water electrolysis that has clean, abundant precursors and zero emission. However, current water electrolysis is hindered by the sluggish kinetics and low cost/energy efficiency of both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). In this regard, electrochemical synthesis offers prospects to raise the efficiency and benefit of water electrolysis by fabricating advanced electrocatalysts and providing more efficient/value-adding co-electrolysis alternatives. It is an eco-friendly and facile fabrication method for materials ranging from molecular to nano scales via electrolysis or other electrochemical operations. In this review, we firstly introduce the basic concepts, design protocols, and typical methods of electrochemical synthesis. Then, we summarize the applications and advances of electrochemical synthesis in the field of electrocatalytic water splitting. We focus on the synthesis of nanostructured electrocatalysts towards more efficient HER, as well as electrochemical oxidation of small molecules to replace OER for more efficient and/or value-adding co-electrolysis with HER. We systematically discuss the relationship between electrochemical synthetic conditions and the product morphology, selectivity to enlighten future explorations. Finally, challenges and perspectives for electrochemical synthesis towards advanced water electrolysis, as well as other energy conversion and storage applications are featured. 氢气是一种清洁、高效、可再生的新型能源，并且是未来碳中和能源供应中最具潜力的化石燃料替代品。 因此，可持续氢能源制造具有极大的吸引力与迫切的需求，尤其是通过清洁、环保、零排放的电解水方法。然而， 目前的电解水反应受到其缓慢的动力学以及低成本/能源效率的制约。在这些方面，电化学合成通过制造先进的电催化剂和提供更高效/增值的共电解替代品，为提高水电解的效率和效益提供了广阔的前景。它是一种环保、简单的通过电解或其他电化学操作，对从分子到纳米尺度的材料进行制造的方法。本文首先介绍了电化学合成的基本概念、设计方法以及常用方法。然后，总结了电化学合成技术在电解水领域的应用及进展。我们专注于电化学合成的纳米结构电催化剂以实现更高效的电解水制氢，以及小分子的电化学氧化以取代电解水制氢中的析氧共反应，实现更高效、增值的共电解制氢。我们系统地讨论了电化学合成条件与产物的关系、以启发未来的探索。最后袁 本文讨论了电化学合成在先进电解水以及其他能量转换和储存应用方面的挑 战和前景。